The political economy of Latin America : reflections on neoliberalism and development - Kingstone, Peter R., 1964- (Routledge, 2011)
This brief text offers an unbiased reflection on the neoliberalism debate in Latin America and the institutional puzzle that underlies the region's difficulties with democratization and development.